Taking Place and Finding One’s Place: Unhomely Events in Mohsin Hamid’s The Reluctant Fundamentalist (2007) and Exit West (2017) - Maëlle Jeanniard du Dot (Sillages Critiques)
In his novels The Reluctant Fundamentalist (2007) and Exit West (2017), Pakistani writer Mohsin Hamid plunges the reader into the core of real-life events through purely fictional material. The characters through which nativist riots or post-9/11 New York are perceived have a specific viewpoint: they are all migrants. Because it is a philosophical and cognitive conundrum, the event mirrors the migrant's experience of the unknown and the unfamiliar, and both the event and the experience of migration end up questioning one's place in the world, one's home, or lack thereof. This paper explores how the phrase "taking place" reflects the identity quests at stake in both novels by Mohsin Hamid. Putting home and event in perspective with, on the one hand, Sigmund Freud's Unheimlichkeit and its narrative manifestations, and, on the other hand, a geographical take on appearance, it discusses how Hamid's migrant subjects channel their multifaceted identities through global events which are at once strange and foreign. Hamid's subtle mingling of realism and fantasy offers an aesthetic vantage point from which the event can be addressed and identities can be negotiated.